1984
DOI: 10.1111/j.2044-8341.1984.tb01597.x
|View full text |Cite
|
Sign up to set email alerts
|

A scale to measure locus of control of behaviour

Abstract: Many behaviour, psychotherapy and healthy life-style programmes require subjects to take responsibility for the control of the old unwanted behaviours or to be responsible for maintaining new desired behaviours after therapy has ended. A scale to measure the locus of control of behaviour would be valuable if it could predict persons likely to relapse following apparently successful therapy. A 17-item Likert-type scale to measure this construct was developed and shown to have satisfactory internal reliability, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
266
4
14

Year Published

1989
1989
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(289 citation statements)
references
References 13 publications
5
266
4
14
Order By: Relevance
“…15 It may be that an internal locus of control can both impede and enhance psychological well-being following SCI. 45,46 In addition, individual personality traits such as achievement, aggression, sociability and stress reaction (as measured by the MPQ and ZPQ in this meta-analysis) were weakly associated with employment. However, this latter finding may also be explained by the fact that personality traits are conceptually defined as stable characteristics, hence less likely to be affected by employment.…”
Section: Discussionmentioning
confidence: 99%
“…15 It may be that an internal locus of control can both impede and enhance psychological well-being following SCI. 45,46 In addition, individual personality traits such as achievement, aggression, sociability and stress reaction (as measured by the MPQ and ZPQ in this meta-analysis) were weakly associated with employment. However, this latter finding may also be explained by the fact that personality traits are conceptually defined as stable characteristics, hence less likely to be affected by employment.…”
Section: Discussionmentioning
confidence: 99%
“…The LCB has acceptable internal reliability (a ¼ 0.79) and construct validity. 11 Higher ratings on each of the aforementioned scales indicate stronger endorsement of the measured construct.…”
Section: Methodsmentioning
confidence: 99%
“…associated with the CD-RISC 10, MSES and LCB reflect the small number of outliers detected for these scales, with 10 individuals (17%) reporting less resilient behaviour (that is, CD-RISC 10 score o20), 15 low selfefficacy (MSES score o60), 10 and/or high externality (LCB score440). 11 In relation to psychological distress (Table 2), most reported subclinical levels of depression (n ¼ 36, 60%; score o10), anxiety (n ¼ 53, 88%; score o8) and stress (n ¼ 49, 82%; score o15), based on the DASS-21 definitions of symptom severity. A small minority (n ¼ 7; 12%) could be defined as clinical 'cases' having reported severe to extremely severe levels of depression (score X21), anxiety (score X15) or stress (score X26).…”
Section: Sample Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of LOC in an spinal cord injury (SCI) sample indicated that persons with recent injuries manifested a more external LOC than an age, gender and education matched able-bodied control group. 2 The researchers reported that 39% of the SCI sample had an external score on the LOC of behavior scale, 3 as compared with 10% of the control group. A follow-up study of a number of the original participants showed by contrast to the 12-month data that there was only a trend for the SCI group to be more externally focused on LOC of behavior scores at 24 months.…”
Section: Introductionmentioning
confidence: 99%